Electrodeposition and Characterization of Ni-Mo-ZrO2 Composite Coatings - Awalludin, Azlan (IRC, 2017)
The Ni-Mo-ZrO2 composite coatings produced by electrodeposition from citrate electrolyte which containing Zirconium Oxide (ZrO2) nanopowder. The influence of the concentration of ZrO2 nanopowder, and Molybdenum content is investigated. The surface structure and corrosion properties of the composite coatings is examined through Scanning Electron Microscopy (SEM) and Linear Polarization Resistance (LPR) test. The increment in Molybdenum content during electrodeposition reduces the ZrO2 in the coating. The presence of ZrO2 changes the surface texture of the material matrix of the coating. The ZrO2 also increases corrosion current density in which improves corrosion resistance overall.